Aquaculture marketing handbook - Engle, Carole Ruth (wiley Blackwell Pub. Professional, 2006)
"Written by authors with vast international aquaculture marketing experience, the Aquaculture Marketing Handbook is an important introduction to aquaculture marketing for those interested in aquaculture and those new to the professional field. The body of knowledge presented in this book will also make it a valuable reference for even the most experienced aquaculture professional."--BOOK JACKET.